Experimental and numerical investigation of the mechanical performance of natural–synthetic hybrid composite laminates - Shaik Irfan Sadaq; Dakuri Vasudev Srividya; Abhishek Agarwal; Balram Yelamasetti; Samera Saniya; Jamyang Choden (PLoS ONE, 2026)
Fiber-reinforced polymer composites have attracted considerable attention in engineering applications owing to their high strength-to-weight ratio, corrosion resistance, and tailorable mechanical properties. Hybridization provides an effective approach for combining the advantageous characteristics of different reinforcement materials to achieve improved overall laminate performance. In the present study, three six-ply hybrid composite laminates, namely J2/C2/J2, J2/G2/J2, and C2/G2/C2, with a [0°/90°] stacking sequence and a relatively high fiber content obtained through controlled hand lay-up fabrication, were fabricated using the hand lay-up technique. Test specimens were prepared according to the relevant ASTM standards and subjected to tensile, compressive, and flexural testing. In addition, finite element simulations were performed using ANSYS Mechanical APDL 2020 R1 to validate the experimental observations. The experimental results demonstrated that natural–synthetic fiber hybridization significantly enhanced the mechanical performance of the investigated laminates. The incorporation of carbon fiber into jute-based laminates resulted in an average strength improvement of approximately 88%, whereas glass-fiber incorporation produced an improvement of approximately 55%. Among the investigated configurations, the C2/G2/C2 laminate exhibited the highest tensile strength (approximately 140 MPa), compressive strength (approximately 39 MPa), and flexural strength (approximately 109 MPa). The numerical predictions showed good agreement with the experimental measurements, with maximum deviations below 1.2%. The results confirm the effectiveness of hybridization in enhancing the mechanical response of composite laminates and identify the C2/G2/C2 configuration as the most promising among the investigated laminate systems. These findings demonstrate the influence of natural–synthetic fiber hybridization on laminate mechanical performance and provide useful information for the design of lightweight composite structural components. Further studies involving pressure-vessel fabrication and internal-pressure testing are required before pressure-vessel applications can be established.